Implementasi Musyawarah Perencanaan Pembangunan Desa (Musrenbangdes) dalam Mewujudkan Pembangunan Partisipatif: Studi di Kabupaten Sleman - Tupen, Devita Larasati; Adzzahra, Fadhia Chalisha; Dewi, Intan Ayu Kusuma; Fatkhuri, Fatkhuri; Pertiwi, Gema (Universitas Muara Bungo, 2025)
This study aims to analyze the effectiveness of the implementation of the Village Development Planning Meeting (Musrenbangdes) in Sleman Regency in realizing participatory development. Using a qualitative method based on literature review, the study examines the implementation of Musrenbangdes through a policy implementation approach, community participation theory, and the concept of participatory development. The analysis was conducted by examining the dynamics of the deliberation process, the involvement of actors, and the extent to which the Musrenbangdes mechanism was able to accommodate the aspirations of residents in village planning. The results of the study show that Musrenbangdes is quite effective in terms of transparency, information dissemination, and aspiration absorption, especially in villages with strong apparatus capacity and good use of information technology. In addition, most of the community's proposals were successfully integrated into planning documents such as the RKPDes and RPJMDes. However, the quality of meaningful participation still faces structural obstacles, including the dominance of local elites in the deliberation process, disparities in community capacity and literacy, and the weak role of the Village Consultative Body (BPD) in carrying out its representative and supervisory functions. Variations in effectiveness between villages are also influenced by social characteristics, local culture, leadership quality, and the ability of village facilitators to create an equitable discussion space. Overall, the study confirms that Musrenbangdes has a strategic role in strengthening participatory development in Sleman, but institutional capacity building, consistent transparency, strengthened oversight, and improved deliberation quality are needed to make the village planning process more inclusive, responsive, and accountable.